Emodin ameliorates renal injury and fibrosis via regulating the miR-490-3p/HMGA2 axis - Wang, Liulin; Wang, Xuerui; Li, Gang; Zhou, Shanshan; Wang, Rui; Long, Qi; Wang, Min; Li, Liang; Huang, Hai; Ba, Yuanming (Frontiers in Pharmacology, 2023)
Renal fibrosis is a major pathological feature of chronic kidney disease (CKD). While emodin is reported to elicit anti-fibrotic effects on renal injury, little is known about its effects on microRNA (miRNA)-modulated mechanisms in renal fibrosis. In this study, we established a unilateral ureteral obstruction (UUO) model and a transforming growth factor (TGF)-β1-induced normal rat renal tubular epithelial cell line (NRK-52E) model to investigate the protective effects of emodin on renal fibrosis and its miRNA/target gene mechanisms. Dual-luciferase assay was performed to confirm the direct binding of miRNA and target genes in HEK293 cells. Results showed that oral administration of emodin significantly ameliorated the loss of body weight and the increase in physicochemical parameters, including serum uric acid, creatinine, and urea nitrogen in UUO mice. Inflammatory cytokines, including tumor necrosis factor-α, monocyte chemoattractant protein-1, and interleukin (IL)-1β, but not IL-6, were down-regulated by emodin administration. Emodin decreased the expression levels of TGF-β1 and fibrotic-related proteins, including alpha-smooth muscle actin , Collagen IV, and Fibronectin, and increased the expression of E-cadherin. Furthermore, miR-490-3p was decreased in UUO mice and negatively correlated with increased expression of high migration protein A2 (HMGA2). We further confirmed the direct binding of miR-490-3p and hmga2. Transfection of miR-490-3p mimics decreased, while transfection of miR-490-3p inhibitors increased fibrotic-related proteins and HMGA2 expression levels in TGF-β1-induced NRK-52E cells. Furthermore, transfection of miR-490-3p mimics enhanced the anti-fibrotic effects of emodin, while transfection of miR-490-3p inhibitors abolished the protective effects of emodin. Thus, as a novel target of emodin that prevents renal fibrosis in the HMGA2-dependent signaling pathway, miR-490-3p has potential implications in CKD pathology.